The EChO science case - Tinetti,G; Drossart,P; Eccleston,P; Hartogh,P; Isaak,K; Linder,M; Lovis,C; Micela,G; Ollivier,M; Puig,L; Ribas,I; Snellen,I; et al. (Experimental Astronomy, 2015)
The discovery of almost two thousand exoplanets has revealed an unexpectedlydiverse planet population. We see gas giants in few-day orbits, whole multi-planet systemswithin the orbit of Mercury, and new populations of planets with masses between that of theEarth and Neptune—all unknown in the Solar System. Observations to date have shown thatour Solar System is certainly not representative of the general population of planets in ourMilky Way. The key science questions that urgently need addressing are therefore: What areexoplanets made of? Why are planets as they are? How do planetary systems work and whatcauses the exceptional diversity observed as compared to the Solar System? The EChO(Exoplanet Characterisation Observatory) space mission was conceived to take up thechallenge to explain this diversity in terms of formation, evolution, internal structure andplanet and atmospheric composition. This requires in-depth spectroscopic knowledge of theatmospheres of a large and well-defined planet sample for which precise physical, chemicaland dynamical information can be obtained. In order to fulfil this ambitious scientificprogram, EChO was designed as a dedicated survey mission for transit and eclipsespectroscopy capable of observing a large, diverse and well-defined planet sample withinits 4-year mission lifetime. The transit and eclipse spectroscopy method, whereby the signalfrom the star and planet are differentiated using knowledge of the planetary ephemerides,allows us to measure atmospheric signals from the planet at levels of at least 10−4 relative tothe star. This can only be achieved in conjunction with a carefully designed stable payloadand satellite platform. It is also necessary to provide broad instantaneous wavelengthcoverage to detect as many molecular species as possible, to probe the thermal structureof the planetary atmospheres and to correct for the contaminating effects of the stellarphotosphere. This requires wavelength coverage of at l